The Routledge International Handbook of Juvenile Homicide: the view from 30,000 feet - Heide, Kathleen M. (The Routledge international handbook of juvenile homicide, 2024)
This chapter provides an overview of The Routledge International Handbook of Juvenile Homicide. This handbook is arranged into 13 parts (sections) and has 48 chapters subsumed under relevant parts. Clinical, theoretical, and empirical components are incorporated into chapters written by leading experts in social sciences, medicine, mental health, and the law from several countries. As a group, these scholars, researchers, clinicians, and practitioners add to the existing literature on juvenile homicide in many ways, including providing cross-national perspectives. Chapter authors also share findings on different types of juvenile homicide offenders (JHOs). Several contributors discuss causes and theoretical explanations of juvenile homicide offending based on research studies and clinical observations. Knowing the causes or pathways to juvenile homicide can be very helpful in designing effective treatment programs and prevention strategies. To this end, contributors discuss specific evidence-based treatment and prevention programs. In light of advances in science about the developmental immaturity of children and adolescents, contributors share research regarding the competency and culpability of JHOs as defendants. Authors also share the experiences and perspectives of incarcerated JHOs using the JHOs’ own words. Other contributors focus on sentencing and ethical considerations, recidivism findings, risk assessment, and prediction of juvenile homicide offending. Authors also make recommendations for policy and practice, including how to shift government policy from punishing lawbreakers to saving lives.